In search of viable standards of culpability for corporate complicity liability in human rights abuses - Mere, Winibaldus Stefanus (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2019)
This paper aims to explore the appropriate and viable standards of actus reus and mens rea to hold corporations liable for complicity in human rights abuses and to clarify the implications of these standards in the context of the UN ‘Protect-respect-remedy’ Framework and Guiding Principles on Business and Human Rights. As the appropriate standards remains in contention, this paper argues that the “substantial effect” and “knowledge” standards constitute the most appropriate and viable standards of the actus reus and mens rea for corporate complicity liability in human rights abuses. Furthermore, these standards are apt to the Framework and Guiding Principles, which require corporations to exercise due diligence to avoid and address complicity issues through concrete acts of “knowing and showing”.